Is ‘Hold Me Tight’ Relationship Enhancement Program Effective in Reducing Fear of Progression in Iranian Married Women with Breast Cancer? - Ali Zargaran; Masoumeh Hedayati (Journal of Muslim Mental Health)
Patients with chronic diseases such as cancer are permanently worried about the progression or recurrence of their diseases. This fear of cancer spreading severely affects a patient’s quality of emotional and marital life. Therefore, this study investigates the effectiveness of the Hold Me Tight (HMT) Relationship Enhancement Program – an EFT-based intervention – on Fear of Progression (FoP) in married women coping with breast cancer. This was a quasi-experimental pre-test–post-test design study with experimental and control groups. Twenty-two couples were recruited and selected purposively among a population of married female patients diagnosed with stage II breast cancer. The couples were assigned into experimental and control groups, each containing 11 couples. The intervention group couples received a 6-session HMT training, and the women in both groups completed the Fear of Progression Questionnaire (FoP-Q ) as pre-test and post-test. We used analysis of covariance to evaluate the effectiveness of the intervention. The statistical analysis results indicated that the mean score of FoP decreased in the experimental group compared to the control group. However, the ANCOVA results revealed no significant difference between the means, showing that the implementation of the HMT intervention program had no significant decreasing effect on FoP dimensions in the intervention group women as compared to the control group (p<0.05). We suggested the consideration of age, relationship satisfaction, the level of FoP before the intervention, cancer stage, and the level of improvement in deciding to use EFT in reducing FoP.